Development of a composite EM wave absorber for the leading edge of low observable aircraft. (24th January 2019) - Lee, Won-Jun; Baek, Sang-Min; Joo, Young-Sik
Abstract : In this study, an Electromagnetic (EM) wave-absorbing composite structure design is proposed. The conventional composite EM wave absorber contains lossy fillers for dielectric characteristics, and thus the fillers affect the mechanical properties, which determine the structural performance of the composite itself. The newly proposed EM wave absorber uses a combination of the following two components: the load-bearable composite structure as the 'shell' and the EM wave-absorbing back layer as the 'absorber.' The shell type absorber does not use any additional fillers in the composite structure. However, the absorbing layer that is designed with a periodic patterned layer and low lossy foam exhibits good EM wave-absorbing performance. Design, analysis with computational simulation, and measurement of EM characteristics are performed to verify the advantages of the shell type absorber. Furthermore, the EM wave absorber is adopted in the leading edge of an aircraft to identify the contribution of Radar Cross Section reduction. This type of absorber has various applications in aerial vehicles, and the EM characteristics are widely tunable for specific purposes without changing the original shell structure.